Effectiveness of Gambir Solution (UncariagambirRoxb) on the Performances of Broiler Chickens were Infected by Escherichia coli. - Dora Villa Manik; Ma'ruf Tafsin; Armyn Hakim Daulay; Nurzainah Ginting; Hasnudi . (Jurnal Peternakan Integratif, 2018)
DORA VILLA MANIK, 2018. "Effectiveness of Gambir Solution(UncariagambirRoxb) on the Performances of Broiler Chickens Infected byEscherichia coli".Supervised by MA'RUF TAFSIN and ARMYN HAKIMDAULAY.Gambir has the potential as an antibacterial which is traditionally used as a drugfor diarrhea. This study examines the effectiveness of gambir solution onperformance which includes feed consumption, body weight gain, feed conversionand income over feed cost (IOFC) in broiler chickens infected with E. coli. It washeld in November - December 2017 at the Laboratory of Biology, AnimalHusbandry Study Program, Faculty of Agriculture University of Sumatera Utara,using a completely randomized design (CRD) with 6 treatments and 3 replications.The treatment consisted of P0A = without infection and without treatment, P0B =infection with E. coli and P1, P2, P3, respectively E. coli infection + Gambirsolution 2%, 4%, 6% and P4 = E. coli + infection Tetracycline antibiotics. Theresults showed that the administration of gambir solution at a dose of 2% - 6% wassignificantly (P<0.05) effective in improving the performances of broiler chickensinfected with E.coli and able to compensate for the use of commercial antibioticsin the form of tetracycline. The highest IOFC is in the 4% gambir solution.Keywords: Gambir, Escherichia coli, and broiler performance.